Tree house mystery eaudiobook - Warner, Gertrude Chandler (The Boxcar Children, 2012)
The Alden children are helping their neighbors build a tree house. From the tree house, the children discover they can see into the attic of the house next door . . . and they notice a window that not even their neighbors know about! Does the old house have a secret?